2020
DOI: 10.1186/s12974-020-01866-6
|View full text |Cite
|
Sign up to set email alerts
|

Slc6a3-dependent expression of a CAPS-associated Nlrp3 allele results in progressive behavioral abnormalities and neuroinflammation in aging mice

Abstract: Background: An association between neuroinflammation and age-related neurologic disorders has been established but the molecular mechanisms and cell types involved have not been thoroughly characterized. Activity of the proinflammatory NLRP3 inflammasome is implicated in Alzheimer's and Parkinson's disease and our recent studies in patients suggest that dopaminergic neurons within the degenerating mesencephalon express NLRP3 throughout the progression of PD. Here, we directly test the impact of enhanced inflam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 81 publications
2
6
0
Order By: Relevance
“…Molecular signatures of this process are evident in human postmortem DA neurons providing pathophysiologic relevance. Consistent with the idea of neuron-specific inflammasome activation is the observation of neuronal activation of the AIM2 inflammasome in synapse elimination during neurodevelopment (Lammert et al, 2020) and the observation of expression of NLRP3 in DA neurons (von Herrmann et al, 2020;von Herrmann et al, 2018) as well as the documentation of neuronal activation of Casp1 in pathologic a-Syn models (Ganjam et al, 2019;Wang et al, 2016). Assembly of the NLRP3 inflammasome complex in PARKIN-deficient hDA neurons did not result in detectable IL-1b or IL-18 secretion, although it did result in increased levels of gasdermin-D cleavage, suggesting that the neurons might be dying via pyroptotic cell death.…”
Section: Discussionsupporting
confidence: 58%
“…Molecular signatures of this process are evident in human postmortem DA neurons providing pathophysiologic relevance. Consistent with the idea of neuron-specific inflammasome activation is the observation of neuronal activation of the AIM2 inflammasome in synapse elimination during neurodevelopment (Lammert et al, 2020) and the observation of expression of NLRP3 in DA neurons (von Herrmann et al, 2020;von Herrmann et al, 2018) as well as the documentation of neuronal activation of Casp1 in pathologic a-Syn models (Ganjam et al, 2019;Wang et al, 2016). Assembly of the NLRP3 inflammasome complex in PARKIN-deficient hDA neurons did not result in detectable IL-1b or IL-18 secretion, although it did result in increased levels of gasdermin-D cleavage, suggesting that the neurons might be dying via pyroptotic cell death.…”
Section: Discussionsupporting
confidence: 58%
“…In that study, Panicker et al further observed elevated expression levels of NLRP3 and the effector protein Caspase-1 in a PD animal model as well and confirmed by immunohistochemistry that the activation of NLRP3 inflammasome suggesting that NLRP3 inflammasome within DANs are activated in a cell-autonomous fashion [ 13 ]. Consistent with this, multiple in vitro models of PD confirm elevated NLRP3 expression in DANs [ 12 , 64 , 65 ]. For the construction of a PD model by treating DANs MES23.5 cells with 6-hydroxydopamine (6-OHDA), for example, elevated NLRP3, ASC, and Caspase-1 protein expression and decreased pro-Caspase-1 protein expression were detected in the model group, suggesting that there is activation of NLRP3 inflammasome in the MES23.5 cells further leading to apoptosis of DANs [ 65 ].…”
Section: Nlrp3 and Pdsupporting
confidence: 63%
“…Moreover, α-synuclein can activate the NLRP3 inflammasome in human microglia [ 111 ]. It has been identified that the L351P NLRP3 mutation contributes to motor abnormalities in animals by activating astrocytes [ 112 ]. However, NLRP3 rs7525979 has been reported as an SNP associated with a significantly reduced risk of developing PD and this synonymous SNP alters the efficiency of NLRP3 translation, thereby affecting NLRP3 protein stability, ubiquitination state, and solubility [ 113 ].…”
Section: Intestinal Dysfunctions In Pdmentioning
confidence: 99%